The Relationship Between Coping Mechanisms With Learning Motivation of Nursing Students At A Private University In Tangerang - Indah Permatasari Meha; Junita Padandi; Laura Naomi Siagian; Maria Veronika Ayu Florensa; Mega Tri Anggraini (Universitas Aisyah Pringsewu, 2022)
Introduction: Students are easy and risky to face stress, so they must have a good coping mechanism to deal with it. Adaptive coping mechanism has a role in motivating their study process. An initial survey of 32 students have, 25% mild stress, 40% moderate and 35% severe. The causes of stress from academic 56% and non-academic 44%. Motivation to learn from internal 34% and external factors 66%, coping mechanisms 66% of them trying to solve any problems they face and 34% just focus on problems. Purpose: To see the relationship between coping mechanisms and learning motivation of nursing students at a Private University in Tangerang. Methodology: The sample of this study amount 294 with purposing sampling, the method uses descriptive correlational. The validated Indonesian version of the Brief Cope Scale and Motivated Strategies for Learning Questionnaire (MSLQ) was used. The result of data analysis with univariate and bivariate analysis. Findings: The results of data of Spearman Rank test obtained p value = 0,636 more than 0,05 indicates that is no significant relationship between coping mechanisms and learning motivation. Originality/ Value/ Implication: This research shows no relationship between coping mechanisms with learning motivation. Students should have a good coping mechanism to manage their stress when face the learning process in Collages.